The Formation of Literary Canon. Literature and Literary History in Morocco - Fernández Parrilla , Gonzalo (Anaquel de Estudios Árabes, 2009)
The process of formation of emerging literatures, as conceptualized by Comparative Literature theorists, is the perfect tool to understand the genesis and development of Modern Arabic Literature, as well as all national Arabic literatures. The formation of modern Moroccan literature and its genres, together with the construction of the notion of “Moroccan literature” by historians and literary critics reveals a highly dynamic and suggestive process where ideology, power and literature intermingle.